RETRACTED: High glucose induced HIF-1α/TREK1 expression and myometrium relaxation during pregnancy - Li, Tengteng; Fei, Jiajia; Yu, Huihui; Wang, Xingxing; Bai, Jingjing; Chen, Fucai; Li, Dan; Yin, Zongzhi (Frontiers in Endocrinology, 2023)
The incidence of gestational diabetes mellitus (GDM) is increasing worldwide. Patients with GDM have a significantly higher rate of cesarean section and postpartum hemorrhage than normal individuals, suggesting changes in uterine contractility. We previously reported on the TWIK-1-related potassium channel (TREK1) expressed in the pregnant uterus and its role in uterine contraction. In this study, uterine tissues were collected from pregnant women with a diagnosis of GDM undergoing elective lower segment cesarean section. We found that the contractility of human uterine strips induced by both KCl and oxytocin was significantly lower in patients with GDM compared with that in normal individuals, with increased TREK1 and hypoxia-inducible factor (HIF)-1α protein expression. The contractility of cultured human uterine smooth muscle cells (HUSMCs) was significantly decreased under high glucose levels, which was consistent with increased expression of HIF-1α and TREK1 proteins. The contractility of HUSMCs was decreased when hypoxia was induced by CoCl2 and increased when hypoxia was inhibited by echinomycin. The TREK1 inhibitor L-methionine also recovered the decreased contractility of HUSMCs under high glucose levels or hypoxia. In conclusion, high glucose levels decreased the contractility of the myometrium, and increased expression of HIF-1α and TREK1 proteins play a role in changes in uterus contractility.